Optimization of Sangju weir operations to mitigate sedimentation problems - Kim, Hwa Young, author; Julien, Pierre Y., advisor; Fontane, Darrell G., committee member; Thornton, Christopher I., committee member; Rathburn, Sara L., committee member (Colorado State University. Libraries, 2016)
To view the abstract, please see the full text of the document.
Keywords: low-head dams; reservoir sedimentation; weirs; Nakdong River; dredging; trap efficiency